Terminally ill patients’ do not resuscitate orders from the doctors’ perspective - Bonamigo, Elcio Luiz (2016)
The do-not-resuscitate order is the explicit statement by patients with advanced disease in progression refusing cardiopulmonary resuscitation. This study aimed to describe the attitude of physicians in relation to the this order and the need for its regulation. A questionnaire was applied to 80 physicians in the medicalbureau of the Regional Council of Medicine of Joacaba/SC, Brazil. It was found that 90% of the respondents knew the meaning of do-not-resuscitate, 86.2% agreed to respect it, 91.2% considered it important to be registered in medical records and 92.5% understood as opportune the issuance of a regulation in this regard.It was concluded that most doctors knew about the do-not-resuscitate order, agreed to respect it, valued its registration in medical records and wanted its regulation by the relevant bodies.